2016
DOI: 10.1136/tobaccocontrol-2016-053118
|View full text |Cite
|
Sign up to set email alerts
|

Use of electronic cigarettes in smoke-free environments

Abstract: Background Although most U.S. states prohibit cigarette smoking in public places and worksites, fewer jurisdictions regulate indoor use of electronic cigarettes (e-cigarettes). Given the dramatic increase in e-cigarette use and concern about its impact on non-users, there is a need to examine the use of e-cigarettes in smoke-free environments and related attitudes and perceptions. Methods Recruited from a nationally representative adult panel (GfK’s KnowledgePanel), 952 current users of e-cigarettes complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 21 publications
2
38
1
Order By: Relevance
“…Our results showed a lower proportion of e-cigarette use in smoke-free places than a previous study conducted in the USA, which reported that 59.5% of e-cigarette users had vaped where cigarette smoking was not allowed 22. We recently estimated that 6.6% of Japanese people have ever used e-cigarettes and 1.3% have used in the last 30 days;23 thus, the prevalence of e-cigarette use is still low in Japan and the impact of e-cigarette use in smoke-free areas may be small so far.…”
Section: Discussioncontrasting
confidence: 85%
“…Our results showed a lower proportion of e-cigarette use in smoke-free places than a previous study conducted in the USA, which reported that 59.5% of e-cigarette users had vaped where cigarette smoking was not allowed 22. We recently estimated that 6.6% of Japanese people have ever used e-cigarettes and 1.3% have used in the last 30 days;23 thus, the prevalence of e-cigarette use is still low in Japan and the impact of e-cigarette use in smoke-free areas may be small so far.…”
Section: Discussioncontrasting
confidence: 85%
“…On the other hand, there are concerns that ecigarettes may be used by smokers to circumvent public use bans on tobacco cigarettes, thus reducing the motivation to quit (Brikmanis, Petersen, and Doran 2017;Damle 2015;Dawkins et al 2013;Filippidis et al 2017;Patrick et al 2016;Pepper and Brewer 2014;Shi, Cummins, and Zhu 2016). Smokers could increase their consumption of nicotine (the primary addicitve ingredient in tobacco cigarettes and e-cigarettes 3 ) and become even more addicted.…”
Section: B Controversy and Regulatory Issues Surrounding E-cigarettesmentioning
confidence: 99%
“…Yingst et al 4 studying a mostly US-based online panel of experienced exclusive e-cigarette users, found that most users reported unrestricted use, but that the majority of those who did find their use restricted by public place policies did not find it difficult to refrain from vaping in such places. Shi et al , in a similar study5 found that e-cigarette users reported vaping in places where cigarettes were not allowed, most often in bars and clubs. They conclude that most e-cigarette users do not consider smoke-free laws applicable to e-cigarettes.…”
mentioning
confidence: 97%